A Compound Heterozygous Mutation in Calpain 1 Identifies a New Genetic Cause for Spinal Muscular Atrophy Type 4 (SMA4) - Perez-Siles, G.; Ellis, M.; Ashe, A.; Grosz, B.; Vucic, S.; Kiernan, M. C.; Morris, K. A.; Reddel, S. W.; Kennerson, M. L. (Frontiers in Genetics, 2022)
Spinal Muscular Atrophy (SMA) is a heterogeneous group of neuromuscular diseases characterized by degeneration of anterior horn cells of the spinal cord, leading to muscular atrophy and weakness. Although the major cause of SMA is autosomal recessive exon deletions or loss-of-function mutations of survival motor neuron 1 (SMN1) gene, next generation sequencing technologies are increasing the genetic heterogeneity of SMA. SMA type 4 (SMA4) is an adult onset, less severe form of SMA for which genetic and pathogenic causes remain elusive. Whole exome sequencing in a 30-year-old brother and sister with SMA4 identified a compound heterozygous mutation (p.G492R/ p.F610C) in calpain-1 (CAPN1). Mutations in CAPN1 have been previously associated with cerebellar ataxia and hereditary spastic paraplegia. Using skin fibroblasts from a patient bearing the p.G492R/ p.F610C mutation, we demonstrate reduced levels of CAPN1 protein and protease activity. Functional characterization of the SMA4 fibroblasts revealed no changes in SMN protein levels and subcellular distribution. Additional cellular pathways associated with SMA remain unaffected in the patient fibroblasts, highlighting the tissue specificity of CAPN1 dysfunction in SMA4 pathophysiology. This study provides genetic and functional evidence of CAPN1 as a novel gene for the SMA4 phenotype and expands the phenotype of CAPN1 mutation disorders.